Vertical changes in shoreline morphology at intra-parasequence scale (Latin American Journal of Sedimentology and Basin Analysis, 2020)
It is commonly assumed in the high-resolution sequence stratigraphic analysis of shallow-marine deposits (e.g., deltaic and shoreface settings) that the depositional conditions of the system remain relatively constant during the transit of a shoreline that would eventually produce a single parasequence. However, based on the detailed sedimentary and architectural analysis of upper-shoreface and foreshore strata of two Early Cretaceous shoreface-shelf parasequences (Neuquén Basin, Argentina), it was possible to document a vertical change through the stratigraphy from deposits representing wave-dominated barred shorelines to deposits interpreted as representing a non-barred morphology. The presence of a well-defined limit between trough cross-bedded sandstones in the upper shoreface and planar laminated sandstones in the foreshore (and the presence of a surf diastem) characterize the development of barred shoreline conditions. Instead, planar lamination is ubiquitous within non-barred deposits, where trough cross-bedding is restricted to the bottomsets of the large-scale inclined beds that characterize this architectural style. Thickness, sediment composition and reconstructed shoreline trajectory also seemingly change vertically within the investigated parasequences. Collectively, these pieces of evidence suggest that the vertical transition from barred to non-barred deposits at this intra-parasequence scale could be related to wave-climate variations and the sequence-stratigraphic context. Specifically, changes in the prevailing wave behavior from dissipative to reflective conditions could be a feasible explanation for the morphological transformation of coastal systems through tens of thousands to hundreds of thousands years.